2015
DOI: 10.3928/00220124-20150721-01
|View full text |Cite
|
Sign up to set email alerts
|

The Elephant in the Room: Nursing and Nursing Power on an Interprofessional Team

Abstract: Notions of competency development frequently underlie discussions of interprofessional education and practice. Yet, by focusing primarily on the development of competencies, the discourse remains at a surface level, thus obscuring the root of many of the tensions that commonly occur in interprofessional collaborative teamwork. This qualitative study explored how perceptions of status influenced participation on an interprofessional team. Findings indicate that underlying tensions exist, despite an overarching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…That both female physicians bought in to the IPRPP, when three out of four male physicians did not, lends some support to the Rebecca's (nursing student) speculation that the pilot's objectives were more compelling for younger, female MDs than their older, male colleagues. Given that the traditional, medical hegemony tends to marginalize not only nurses, but women (Bell, Michalec, & Arenson, 2014;Hart, 2015;Price, Doucet, & Hall, 2014;Price, Hall, Angus, & Peter, 2013), the female MDs perhaps embraced the pilot as a means of advancing both gender-and disciplinary parity. Thus, while lack of buy-in by more experienced, male MDs may have deprived some students of richer IP experiences, it also provoked fruitful and timely reflections about power and clinical culture, which added value to the pilot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That both female physicians bought in to the IPRPP, when three out of four male physicians did not, lends some support to the Rebecca's (nursing student) speculation that the pilot's objectives were more compelling for younger, female MDs than their older, male colleagues. Given that the traditional, medical hegemony tends to marginalize not only nurses, but women (Bell, Michalec, & Arenson, 2014;Hart, 2015;Price, Doucet, & Hall, 2014;Price, Hall, Angus, & Peter, 2013), the female MDs perhaps embraced the pilot as a means of advancing both gender-and disciplinary parity. Thus, while lack of buy-in by more experienced, male MDs may have deprived some students of richer IP experiences, it also provoked fruitful and timely reflections about power and clinical culture, which added value to the pilot.…”
Section: Discussionmentioning
confidence: 99%
“…That these two professions remain stubbornly gendered (Seenandan-Sookdeo, 2012), particularly in the underrepresentation of women in senior medical positions (Bell, Michalec, & Arenson, 2014), is an additional barrier to collaboration and IPE. Inroads in IPE notwithstanding, nurses and other members of the IP team still act out a normative discourse in which nurses have a lower status than other team members (Hart, 2015;Price, Doucet, & Hall, 2014;Price, Hall, Angus, & Peter, 2013;Seenandan-Sookdeo, 2012), with negative implications for the socialization of students on practicum. Kuper and Whitehead (2012) question the effectiveness of IPE in promoting collaboration, insofar as physician-educators have a vested interest in maintaining the status quo.…”
Section: Cultural Barriers To Ipementioning
confidence: 99%
“…Existen importantes barreras que dificultan la colaboración entre profesionales: problemas de comunicación entre profesionales [5][6][7][8][9][10][11][12] , el desconocimiento de las funciones y responsabilidades profesionales del otro [5][6][7][12][13][14] , el poder y la jerarquía 5,6,[13][14][15][16] , la falta de confianza (en el otro) 5,6 e incluso la falta de respeto 5,6,8 . Para superar estas barreras es especialmente importante la implantación real de reuniones interprofesionales 2,5,10,17,18 , pues la ausencia, real o de facto, de algunos colectivos en estas reuniones (en las que se decide la atención al paciente) es todavía frecuente 6,7,15 .…”
Section: Introductionunclassified
“…Negative attitudes or stereotypes towards other health professions are associated with gender, social status, prior knowledge of IPE, "silo" approaches to teaching, and professional culture. Negative stereotypes still present significant barriers to collaboration, and researchers insist on the need to address power relations between health professionals (Ateah et al 2011;Hart, 2015). For example, Curran, Sergeant, and Hollett (2007) reported that men scored significantly lower on their attitude score than did females, suggesting that gender plays a role in an individual's attitudes toward IPE.…”
Section: Challenges Of Interprofessional Health Educationmentioning
confidence: 99%
“…Ateah et al (2011) underscore that the view of a nurse as a "jack of all trades" undermines the nursing-specific contributions in practice settings. Hart (2015) suggests addressing nurses' disempowerment through critical empowerment strategies like critical thinking and conflict management activities. Critical empowerment strategies reveal the relations of power within interprofessional teams and help nurses to understand how to manage power dynamics within teams.…”
Section: Individual Barriersmentioning
confidence: 99%